Computing force network technologies for computing and network integration evolution - Xiaodong DUAN; Huijuan YAO; Yuexia FU; Lu LU; Tao SUN (Dianxin kexue)
With the construction of the national hub node of the integrated computing force network and the accelerated implementation of the “eastern data and western calculation” project, the integration of computing and network is moving towards the deep water area. Facing the needs of emerging businesses for networks and computing, how to coordinate distributed computing resources, service applications and network resources to meet service needs has become an urgent problem to be solved. Aiming to solve the problems of computing and network awareness, coordination, and scheduling. The key technologies, including phased evolution of computing force network , computing-aware technology architecture, computing force quantity and identification, computing force routing and other technologies were explored and researched, and a variety of deployment modes of computing force network was proposed, and reference was provided for the follow-up technology research and industry development of the computing force network.